Heavy metal mediated innate immune responses of the Indian green frog, Euphlyctis hexadactylus (Anura: Ranidae): Cellular profiles and associated Th1 skewed cytokine response - Jayawardena, Uthpala A.; Ratnasooriya, Wanigasekara D.; Wickramasinghe, Deepthi D.; Udagama, Preethi V. (Science of The Total Environment, 2016)
Immune cell and cytokine profiles in relation to metal exposure though much studied in mammals has not been adequately investigated in amphibians, due mainly to lack of suitable reagents for cytokine profiling in non-model species. However, interspecies cross reactivity of cytokines permitted us to assay levels of IFNγ, TNFα, IL6 and IL10in a common anuran, the Indian green frog (Euphlyctis hexadactylus), exposed to heavy metals (Cd, Cr, Cu, Zn and Pb, at ~ 5 ppm each) under field and laboratory settings in Sri Lanka. Enumeration of immune cells in blood and melanomacrophages in the liver, assay of serum and hepatic cytokines, and Th1/Th2 cytokine polarisation were investigated. Immune cell counts indicated overall immunosuppression with decreasing total WBC and splenocyte counts while neutrophil/lymphocyte ratio increased with metal exposure, indicating metal mediated stress. Serum IL6 levels of metal exposed frogs reported the highest (~ 9360 pg/mL) of all cytokines tested. Significantly elevated IFNγ production (P < 0.05) was evident in heavy metal exposed frogs. Th1/Th2 cytokine ratio in both serum and liver tissue homogenates was Th1 skewed due to significantly higher production of pro-inflammatory cytokines, IFNγ in serum and TNFα in the liver (P < 0.01).Metal mediated aggregations of melanomacrophages in the liver were positively and significantly (P < 0.05) correlated with the hepatic expression of TNFα, IL6 and IL10 activity. Overall, Th1 skewed response may well be due to oxidative stress mediated nuclear factor κ-light chain enhancer of activated B cells (NFκB) which enhances the transcription of pro-inflammatory cytokines. Xenobiotic stress has recently imposed an unprecedented level of threat to wildlife, particularly to sensitive species such as amphibians. Therefore, understanding the interactions between physiological stress and related immune responses is fundamental to conserve these environmental sentinels in the face of emerging eco-challenges.
Highlights • Heavy metal pollution in wetland ecosystem is a serious ecotoxicological issue of global dimension • Immune cells and cytokine profile alternations were detected in heavy metal exposed Euphylictis hexadactylus under field and laboratory conditions • Th1 immune response showed significant positive correlation with neutrophil counts explaining the role of neutrophil function under heavy metal burden. • Heavy metal mediated inflammatory response in the liver elevated TNFα, IL6 and IL10 production, positively correlated with melanomacrophage aggregates • Th1 skewed immune response may be attributed to oxidative stress mediated NFκB activation
Keywords: Heavy metal; Euphlyctis hexadactylus; Th1 skewed cytokine